THE ROLE OF PARENTS IN EARLY CHILDHOOD ISLAMIC EDUCATION: A HOLISTIC APPROACH - Siti Rozinah; Saiful Bahri; Suci Siti Nurbarkah (JURNAL PENDIDIKAN GLASSER, 2024)
Early childhood education in an Islamic perspective plays an important role in shaping children's character and spiritual values. This study aims to analyze the role of parents in early childhood Islamic education through a holistic approach in PAUD KB Amanah. The method used is a descriptive qualitative approach with in-depth interviews, observation, and documentation as data collection instruments. The results showed that parents' involvement in early childhood Islamic education at PAUD KB Amanah. The holistic approach applied includes integrating Islamic values education, social skills and children's cognitive development in a balanced manner. This research underscores the importance of synergy between parents and educational institutions in providing a solid spiritual foundation for children. The findings are expected to serve as a model in the implementation of family-based early childhood Islamic education in other PAUD institutions.